The experience of decision making in the care of children with palliative care needs: the experiences of Jordanian mothers - Atout, Maha; Hemingway, Pippa; Seymour, Jane (Taylor & Francis, 2017)
The purpose of this study was to explore the experience of decision making in the care of children with palliative care needs in Jordan, from the perspective of their mothers. This study employed a collective qualitative case study approach. Data were collected in 3 pediatric wards in a Jordanian hospital. The study used 2 data collection methods: participant observation (197 observational hours) and 56 semi-structured interviews with 24 mothers, 12 physicians and 20 nurses. The findings show how Jordanian mothers seek to transfer the role of decision making to physicians, as they perceive themselves to be unable to make decisions about critical issues related to the treatment of their children. Mothers had a widespread apprehension of “future guilt,” especially when they feared that any decisions they might make could have an adverse impact on their children. Contrary to the predominant pattern, some mothers took a proactive approach towards decision making about their children’s treatment. These mothers requested detailed information from primary physicians and sought different sources of knowledge such as second opinions, reading online resources, or talking to other parents who had a child with similar circumstances. The study concludes that mothers prefer to involve physicians in decisions about their children’s healthcare and treatment to eliminate their fear of probable future guilt; this modifies any tendency to autonomously decide for their children. These findings are underpinned by the Jordanian culture in which doctors’ opinions are highly regarded.